A Preliminary In-situ TEM Study of Martensite/Austenite Interface Migration in an Fe-20Ni-5.4Mn Alloy. (2015) - Mompiou, F.; Wu, J.; Zhang, W.-Z.
Abstract: We report an in-situ TEM investigation of a reverse martensite transformation in an Fe–Ni–Mn alloy at temperature ranging from 400 °C to 600 °C. Two modes, normal and ledge motions, have been observed during retreating migration of the broad interfaces (∼habit plane) between austenite and martensite. A large number of dislocations nearly perpendicular to the interface were observed in the volume swept by a fast normal motion of the interface, while few dislocations are left behind in the fresh austenite transformed by a ledge motion. During the ledge motion, concurrent displacement of the interfacial dislocations along both ledge riser and terrace plane is evidently detected. The normal displacement component for the dislocations in the broad interface is small and this is associated with a slow normal motion of the interface.